2011
DOI: 10.1002/mnfr.201100240
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐resveratrol simultaneously increases cytoplasmic Ca2+ levels and nitric oxide release in human endothelial cells

Abstract: We therefore show, for the first time, that t-Resv induces a concentration-dependent, simultaneous increase in [Ca(2+)](c) and NO biosynthesis that could be linked to its endothelium-dependent vasorelaxant effect. Under the assumption that t-Resv exhibits similar behaviour in human blood vessels in vivo, the pharmacological properties described here may contribute to the beneficial cardiovascular effects of this polyphenol by improving endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 51 publications
3
26
1
Order By: Relevance
“…Nevertheless, its capacity of inhibiting oxygen free radical formation may come from the inhibition of reactive oxygen species (ROS) production by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOX) [78,79] and by the induction of antioxidative enzymes or their substrates, such as superoxide dismutase (SOD) [78,80-83], thioredoxin [84], heme oxygenase-1 (HO-1) [84- 87], glutathione peroxidase-1 (GPx1) [78,80] and catalase [81]. According to the published evidence, RES has the capacity to improve endothelium function mainly by stimulating endothelial production of nitric oxide (NO) [88-91] through multiple mechanisms, particularly by enhancing endothelial nitric oxide synthase (eNOS) expression and/or activity [88,92-94] even at physiological concentrations [89,90,95] (Supplementary Table ). It has been suggested that RES enhances eNOS activity via 5’-adenosine monophosphate-activated protein kinase (AMPK) or extracellular signal-regulated kinase 1/2 (ERK1/2)-mediated phosphorylation at Ser1177 [90,96].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Nevertheless, its capacity of inhibiting oxygen free radical formation may come from the inhibition of reactive oxygen species (ROS) production by nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOX) [78,79] and by the induction of antioxidative enzymes or their substrates, such as superoxide dismutase (SOD) [78,80-83], thioredoxin [84], heme oxygenase-1 (HO-1) [84- 87], glutathione peroxidase-1 (GPx1) [78,80] and catalase [81]. According to the published evidence, RES has the capacity to improve endothelium function mainly by stimulating endothelial production of nitric oxide (NO) [88-91] through multiple mechanisms, particularly by enhancing endothelial nitric oxide synthase (eNOS) expression and/or activity [88,92-94] even at physiological concentrations [89,90,95] (Supplementary Table ). It has been suggested that RES enhances eNOS activity via 5’-adenosine monophosphate-activated protein kinase (AMPK) or extracellular signal-regulated kinase 1/2 (ERK1/2)-mediated phosphorylation at Ser1177 [90,96].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…These interesting properties confer the cardiovascular protective capacity and ability to protect endothelial function on resveratrol [19], [20]. In cancer patients, resveratrol exhibits anticancer properties, such as suppression of tumor cell proliferation, induction of tumor cell apoptosis, increase in chemosensitization of tumor cells, and exerts chemopreventive effects [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…They assume that if it would act in the same way in human blood vessels in vivo, the pharmacological properties observed might contribute to the beneficial cardiovascular effects of this polyphenol by improving endothelial function. 9 The polyphenolic natural product resveratrol is considered to have potential as a drug for prevention and treatment of cardiovascular diseases (CVDs). A review published in Biofactors summarizes the molecular effects of resveratrol on endothelial cells that play a key role in the development of those diseases: Resveratrol enhances endothelial NO production, improves endothelial redox balance, and inhibits endothelial activation in response to pro-inflammatory and metabolic factors.…”
Section: Resveratrol Enhances Nitric Oxide Biosynthesis Andmentioning
confidence: 99%